2003
DOI: 10.1189/jlb.0403156
|View full text |Cite
|
Sign up to set email alerts
|

Drug-loaded red blood cell-mediated clearance of HIV-1 macrophage reservoir by selective inhibition of STAT1 expression

Abstract: Current highly active antiretroviral therapy (HAART) cannot eliminate HIV-1 from infected persons, mainly because of the existence of refractory viral reservoir(s). Beyond latently-infected CD4+-T lymphocytes, macrophages (M/M) are important persistent reservoirs for HIV in vivo, that represent a major obstacle to HIV-1 eradication. Therefore, a rational therapeutic approach directed to the selective elimination of long-living HIV-infected M/M may be relevant in the therapy of HIV infection. Here we report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 49 publications
0
39
0
2
Order By: Relevance
“…SM RBC were loaded with fludarabine by a procedure involving hypotonic dialysis, isotonic resealing, and reannealing, as previously described (28). Some modifications were performed to adapt the procedure for SM RBC.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…SM RBC were loaded with fludarabine by a procedure involving hypotonic dialysis, isotonic resealing, and reannealing, as previously described (28). Some modifications were performed to adapt the procedure for SM RBC.…”
Section: Methodsmentioning
confidence: 99%
“…Cytoplasmic STAT proteins are activated by tyrosine phosphorylation, a transient and tightly regulated process that results in dimerization, nuclear translocation, and transcriptional activation of genes that control the cellular response (2,27,41). We found that levels of phosphorylated STAT1 (pSTAT1) were three-to fivefold greater in in vitro HIV-infected M/M compared to uninfected M/M (28). Therefore, we proposed that, at least in this in vitro system, the enhanced expression and phosphorylation of STAT1 may play a role in the development of a persistent state of active HIV replication in M/M.…”
mentioning
confidence: 98%
See 3 more Smart Citations